Sengketa Pers: Pencemaran Nama Baik Menurut UU ITE dan UU Pers - Ramadana; Siti Rahma; Syariffuddin (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study examines legal issues regarding press disputes arising from alleged defamation in online media, which often lead to legal uncertainty and the risk of criminalization against journalists. The objectives are to analyze applicable legal provisions and formulate dispute resolution mechanisms consistent with the principles of press freedom and professional responsibility. This research uses a normative legal method with statutory, conceptual, and case approaches. The findings reveal overlapping regulations between the Electronic Information and Transactions Law as general law and the Press Law as specific law. Under the principle of lex specialis derogat legi generali, journalists working in accordance with journalistic standards shall have their disputes resolved through non-criminal procedures at the Press Council. In contrast, reporting that fails to meet professional standards may be subject to general legal provisions. It is concluded that press disputes should be prioritized for resolution through the Press Council mechanism, while criminal law may only be applied if malicious intent or false information is proven.